Adsorption Studies of the Effect of Thiosemicarbazides on the Corrosion of Steel in Phosphoric Acid - M.A. Ameer; E. Khamis; G. Al-Senani (Adsorption Science & Technology)
The corrosion inhibition of steel in phosphoric acid by thiosemicarbazide derivatives has been studied using different chemical and electrochemical techniques. The observed order of increasing inhibition efficiency was correlated with changes in the molecular structures of the inhibitors. Potentiodynamic polarization curves indicate that the compounds are mixed-type inhibitors. Electrochemical impedance spectroscopy has been used successfully to evaluate the performance of the inhibitors. AC measurements showed that the dissolution process was activation-controlled. The kinetic–thermodynamic model and the Flory–Huggins adsorption isotherm described the experimental findings well. The number of active sites, binding constant and change in free energy were computed for all the inhibitors studied. It was found that the inhibitor molecule was adsorbed through more than one active centre and occupied more than one active site on the steel surface.